2015
DOI: 10.12659/msm.894184
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulating Receptor Interacting Protein Kinase 1 (RIP1) Promotes Oxaliplatin-Induced Tca8113 Cell Apoptosis

Abstract: BackgroundOxaliplatin is a crucial chemotherapy drug that plays an important role in colorectal cancer and oral cancer treatment. However, the molecular mechanism of oxaliplatin in killing tongue squamous cell cancer cells is still unknown. This paper investigates the mechanism of by which oxaliplatin regulates tongue squamous cell carcinoma Tca8113 cell survival and death.Material/MethodsTca8113 was treated with 1 μmol/L oxaliplatin for 24 h. Tca8113 cell proliferation and apoptosis were determined by MTT met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…46 Downregulation of RIPK1 promotes oxaliplatin-induced Tca8113 cell apoptosis. 47 The current study provides evidence that after treatment with miR-590-3p mimic, the expression level of NF-κB was decreased, and OS and inflammatory response were alleviated. Consistently, miR-590-3p transfection downregulates the activity of NF-κB and promotes cardiac function in experimental autoimmune myocarditis.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…46 Downregulation of RIPK1 promotes oxaliplatin-induced Tca8113 cell apoptosis. 47 The current study provides evidence that after treatment with miR-590-3p mimic, the expression level of NF-κB was decreased, and OS and inflammatory response were alleviated. Consistently, miR-590-3p transfection downregulates the activity of NF-κB and promotes cardiac function in experimental autoimmune myocarditis.…”
Section: Discussionmentioning
confidence: 52%
“…It is found that RIPK1 works as a potent promoter of cell apoptosis, and RIPK1 can also regulate NF‐κB and is likely necessary for NF‐κB activation . Downregulation of RIPK1 promotes oxaliplatin‐induced Tca8113 cell apoptosis …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it's also actively researched in castration resistant prostate cancer patients (29,30). Our data indicated that even cancer cells are resistant to ADT, they can be sensitive to chemotherapy, such as oxaliplatin due to its non-targeted cell death induction roles (31). In our syngeneic animal model of prostate cancer, either oxaliplatin or anti-PD-1 Ab increased overall survival marginally.…”
Section: Discussionmentioning
confidence: 68%
“…The present study is mainly limited by the lack of a comprehensive analysis of multiple proteins that could be involved in the effects of PARD3 expression on carcinogenesis of ESCC, such as connective tissue growth factor [ 30 ], interacting protein kinase 1 [ 31 ], cofilin-1, and transgelin [ 32 ]. In addition, only the PARD3 protein was studied, and there could be some discrepancies between transcription and translation.…”
Section: Discussionmentioning
confidence: 99%